2013
DOI: 10.4103/0973-029x.125197
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical expression of Src protein in peripheral and central giant cell granulomas of the jaws

Abstract: Aim and Objective:The aim of this study was to investigate the expression of Src protein (an osteoclastic factor) in peripheral and central giant cell granulomas (PGCG and CGCGs) of the jaws and the relationship between the expression of this protein and the clinical behavior of these two lesions.Materials and Methods:Thirty cases of PGCG and 30 cases of CGCG were immunohistochemically stained with Src. A staining-intensity-distribution (SID) score (proportion of stained cells × staining intensity) was used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 19 publications
(32 reference statements)
0
4
0
Order By: Relevance
“…Twenty-one studies were mainly associated with behaviour of GCLs of jaws [ Table 3 ]. [ 5 8 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 ]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty-one studies were mainly associated with behaviour of GCLs of jaws [ Table 3 ]. [ 5 8 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 ]…”
Section: Resultsmentioning
confidence: 99%
“…Khiavi et al . [ 42 ] reported that osteoclastic protein (Src) does not reflect the distinct clinical behaviour of PGCG and CGCG. Martini et al .…”
Section: Discussionmentioning
confidence: 99%
“…This study sought to assess the biological behaviour of giant cell granulomas of jaw through histomorphometric analysis. On the other hand, there are various studies in literature that have used various histochemical markers like AgNOR, CD68, vascular endothelial growth factor (VEGF), Ki-67, p53, osteopontin, integrin α v , Src protein, TRAP (tartrateresistant acid phosphatase), Mouse Double Minute 2 homolog (MDM2), Proliferating Cell Nuclear Antigen (PCNA), factor XIII, MMP-2, MMP-9, CD105, CD34, CD31, Cathepsin D [2,5,15,[18][19][20][21]. However, there is no consensus amongst the authors regarding the role of these histochemical markers in determining the behaviour of giant cell granulomas of jaw; hence, we are planning to conduct a study in future using some of these markers to clarify their role in assessing the behaviour of these two lesions.…”
Section: Discussionmentioning
confidence: 99%
“…However, the understanding of the possible origin of this lesion is a very important issue to manage and control these disease. [ 1 2 21 22 ] Studies on giant-cell granulomas have recently shifted toward mononuclear cells, since many investigators believe that mononuclear cells are the proliferative component of these lesions and are responsible for their biological behavior. Several studies have suggested that the cellular component shows characteristics of osteoclast progenitor cells, macrophages, myofibroblasts endothelial cells, or fibroblasts.…”
Section: Discussionmentioning
confidence: 99%